Retention of endoscopic capsules in diverticula: Literature review of a capsule endoscopy rarity - Thorndal, Camilla; Selnes, Ola; Lei, Ian Io; Schostek, Sebastian; Koulaouzidis, Anastasios (Endoscopy International Open, 2024)
Background and study aims This review aimed to provide an updated and comprehensive review of capsule retention within diverticula, shedding light on the characteristics and management of this rare event in capsule endoscopy.Methods A systematic literature search was conducted across multiple databases. All observational studies that reported capsule retention in a diverticulum among complication and outcomes, as well as case reports and series, were included. Manual cross-checking of references was also performed. Two extractors performed abstract and full-text reviews, as well as data-extraction.Results We found 167 references from Pubmed, Embase, and Web Of Science. Sixty-five duplicates were removed and another 71 references were excluded. Crosschecking of references found additional two articles. In total, 32 articles were included, resulting in a total of 34 cases of retained capsules in diverticula. The median age was 69 and the majority of the patients were male (76.5%). The most common retention occurred in Meckel’s diverticulum (32.4%) followed by Zenker’s diverticulum (20.6%). Investigation of capsule retention was done with x-ray (50%) and computed tomography (CT) scan (44.1%). Seventeen cases (50%) were asymptomatic. Resolution of the retention happened with endoscopy (35.3%) and surgical management (32.4%), as well as self-resolution (20.6%).Conclusions Due to the small number of cases, diverticula are not a risk factor for incomplete capsule endoscopy examination. It affects mainly elderly, male, asymptomatic patients, and typically is diagnosed with x-rays and CT scans. The most common type is Meckel’s diverticulum, and endoscopy is the primary management. Capsule endoscopy retentions are extremely rare, with only 34 cases reported since the technology's introduction.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Endoscopy Upper GI Tract; Endoscopy Lower GI Tract